Assessment of the Legal and Regulatory Framework for Foreign Direct Investment : Mozambique - World Bank Group (World Bank, Washington, DC, 2021)
In more recent years, new investments reinforced the megaproject growth model. At present, it is envisaged that the country will experience unprecedented investments in the next 30 years. Realizing the full potential of large oil and gas investments will require a shift in Mozambique’s development strategy to date. Foreign direct investment (FDI) is a critical source of finance in Mozambique, supporting the country’s growth through the development of megaprojects in extractives and infrastructure. The strong focus on financing FDI through debt instruments likely reflects the specificities of megaprojects and the little confidence investors have in the country’s investment climate. Given the impact the Coronavirus disease 2019 (COVID-19) crisis has had on FDI in Mozambique, the government should focus on putting the foundations for investment competitiveness in place to support a resilient recovery. FDI-related recovery support also includes the promotion of links with megaprojects. This report serves as a background paper to the country private sector diagnostic of Mozambique. The report assesses the legal and regulatory framework for FDI with a view to formulate actionable recommendations for consideration by the government.